Possible Roles for Basal Levels of (p)ppGpp: Growth Efficiency Vs. Surviving Stress - Fernández-Coll, Llorenç; Cashel, Michael (Frontiers in Microbiology, 2020)
Two (p)ppGpp nucleotide analogs, sometimes abbreviated simply as ppGpp, are widespread in bacteria and plants. Their name alarmone reflects a view of their function as intracellular hormone-like protective alarms that can increase a hundred-fold when sensing any of an array of physical or nutritional dangers, such as abrupt starvation, that trigger lifesaving adjustments of global gene expression and physiology. The diversity of mechanisms for stress-specific adjustments of this sort is large and further compounded by almost infinite microbial diversity. The central question raised by this review is whether the small basal levels of (p)ppGpp functioning during balanced growth serve very different roles than alarmone-like functions. Recent discoveries that abrupt amino acid starvation of E. coli, accompanied by very high levels of ppGpp, occasion surprising instabilities of tRNA, rRNA and ribosomes raises new questions. Is this destabilization a mode of regulation linearly related to (p)ppGpp over the entire continuum of (p)ppGpp levels, including balanced growth? Are regulatory mechanisms exerted by basal (p)ppGpp levels fundamentally different than for high levels? There is evidence from studies of other organisms suggesting special regulatory features of basal levels compared to burst of (p)ppGpp. Those differences seem to be important even during bacterial infection, suggesting that unbalancing the basal levels of (p)ppGpp may become a future antibacterial treatment. A simile for this possible functional duality is that (p)ppGpp acts like a car’s brake, able to stop to avoid crashes as well as to slow down to drive safely.